Digital Payment Integration and Financial Control in Large Educational Institutions: A Qualitative Case Study of an Islamic Boarding School Ecosystem - M. Sholihun; Mochamad Sirojuddin; Sri Mulyani; Mohammad Yusuf Wijaya; Ismailova Zukhra Karabaevna (Sharia Economic and Management Business Journal (SEMBJ), 2026)
Background: The financial management of large educational institutions often faces challenges related to payment accuracy, data reconciliation, and administrative efficiency, particularly when transactions are conducted manually or through semi-digital systems. This study examines the transformation of financial management through the implementation of an integrated digital payment system in a large Islamic boarding school ecosystem serving approximately 11,000 students across multiple educational units. Method: Using a qualitative case study approach, data were collected through in-depth interviews with financial administrators, information technology staff, and customer service personnel, as well as through document analysis and process observation. The findings reveal that the adoption of an integrated digital payment application significantly improves transaction accuracy, financial recording reliability, and billing transparency by eliminating manual confirmation and reducing human error. Moreover, the establishment of dedicated customer service teams at each educational unit plays a critical role in facilitating digital payment adoption, particularly in addressing limitations related to banking access and digital literacy among students’ guardians. Results: This study contributes to the financial management and digital finance literature by highlighting the importance of organizational support mechanisms in ensuring the effectiveness of digital payment systems within large, non-profit educational institutions. The findings offer practical insights for policymakers and educational managers seeking to enhance financial control and accountability through digital transformation. Conclusion: The study reveals that technological integration alone is insufficient to ensure effective financial transformation. Organizational support mechanisms particularly dedicated customer service units played a critical role in facilitating system adoption and sustaining daily financial operations.